Biological Control of Plant-Parasitic Nematodes: 2011
DOI: 10.1007/978-1-4020-9648-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Plant Nematode Surfaces

Abstract: The outer surface of nematodes act as an external skeleton and is covered by a tough, but flexible, multi-layered, extracellular cuticle which protects them from the external environment, maintains body shape and is involved in locomotion and defence against their host or microorganism attack. This chapter highlights the role of the nematode surface cuticle, during the various life-stages, with their environment, including their host and other microorganism. A comprehensive appraisal is presented of the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…It is known that bacteria produce metabolites and hydrolytic enzymes that may have nematicidal effects (Curtis et al . ), and they have been reported in several studies, mainly on species of Meloidogyne (Siddiqui et al . ; Li et al .…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…It is known that bacteria produce metabolites and hydrolytic enzymes that may have nematicidal effects (Curtis et al . ), and they have been reported in several studies, mainly on species of Meloidogyne (Siddiqui et al . ; Li et al .…”
Section: Introductionmentioning
confidence: 67%
“…The better characterized and more abundant proteins in the nematode cuticle are the different collagen types (Curtis et al . ). In the genome of M. incognita , there are 122 genes coding for collagens (Abad et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter indirect effect provides evidence supporting the hypothesis of Kaplan and Davis (), who suggested that the nematode surface coat plays a role in plant–nematode interactions. The surface coat has been an active area of research for several decades and is thought to play a role in nematode–plant interactions, as it is known to be readily shed and replaced both outside and within the roots (Curtis et al ., ; Davies and Curtis, ; Gravato‐Nobre et al ., ; Lin and McClure, ; Spiegel and McClure, ). Interestingly, the most dominant model for the description of plant–pathogen interactions is the zig‐zag model of coevolution between microbial‐associated molecular patterns (MAMPs), secreted/excreted by the pathogen, and pattern recognition receptors (PRRs), which, in turn, ultimately leads to either a susceptibility or resistance response of the host (Jones and Dangl, ).…”
Section: Discussionmentioning
confidence: 99%